Constraining 20th‐Century Sea‐Level Rise in the South Atlantic Ocean. Issue 3 (12th March 2021) - Frederikse, Thomas; Adhikari, Surendra; Daley, Tim J.; Dangendorf, Sönke; Gehrels, Roland; Landerer, Felix; Marcos, Marta; Newton, Thomas L.; Rush, Graham; Slangen, Aimée B. A.; Wöppelmann, Guy
Abstract: Sea level in the South Atlantic Ocean has only been measured at a small number of tide‐gauge locations, which causes considerable uncertainty in 20th‐century sea‐level trend estimates in this basin. To obtain a better‐constrained sea‐level trend in the South Atlantic Ocean, this study aims to answer two questions. The first question is: can we combine new observations, vertical land motion estimates, and information on spatial sampling biases to obtain a likely range of 20th‐century sea‐level rise in the South Atlantic? We combine existing observations with recovered observations from Dakar and a high‐resolution sea‐level reconstruction based on salt‐marsh sediments from the Falkland Islands and find that the rate of sea‐level rise in the South Atlantic has likely been between 1.1 and 2.2 mm year −1 (5%–95% confidence intervals), with a central estimate of 1.6 mm year −1 . This rate is on the high side, but not statistically different compared to global‐mean trends from recent reconstructions. The second question is: are there any physical processes that could explain a large deviation from the global‐mean sea‐level trend in the South Atlantic? Sterodynamic (changes in ocean dynamics and steric effects) and gravitation, rotation, and deformation effects related to ice mass loss and land water storage have probably led to a 20th‐century sea‐level trend in the South Atlantic above the global mean. Both observations and physical processes thus suggest that 20th‐century sea‐level rise in the South Atlantic has been about 0.3 mm year −1 above the rate of global‐mean sea‐level rise, although even with the additional observations, the uncertainties are still too large to distinguish a statistically significant difference. Plain Language Summary: Before the satellite era, we depend on the tide‐gauge network to measure sea‐level changes. In the North Atlantic and Pacific Oceans, many tide gauges have been installed, but there are only a handful in the South Atlantic Ocean. Because of this, it is challenging to accurately determine 20th‐century sea‐level changes in the South Atlantic. Because the South Atlantic Ocean covers about one‐fifth of the global oceans, estimates of global sea‐level changes are also affected by the low number of observations in the South Atlantic. Here, we try to improve this situation by adding recently rescued tide‐gauge observation data from Dakar and a new paleo record that has been derived from a salt marsh in the Falklands to the existing sea‐level records. We find that since 1900, South Atlantic sea level has likely risen slightly faster than the global average. This above‐average rate makes sense, because thermal expansion in the South Atlantic has likely been faster than the global mean, and mass loss from ice sheets and glaciers results in above‐average sea‐level rise in the South Atlantic. Key Points: We estimate 20th‐century sea‐level changes in the South Atlantic Ocean from tide‐gauge data and a new paleo proxy 20th‐century sea‐level rise in the South Atlantic might have been above the global mean, but uncertainties remain large Estimates of contemporary mass redistribution and sterodynamic effects support this above‐average trend